Strategi Pemanfaatan Teknologi dan Inovasi Untuk Meningkatkan Keberlanjutan UMKM Sari Tebu Nal di Kota Parepare - Sudarmono, Sudarmono; Putra, Ririn Ade; Ilahi, Andi Alfianto Anugrah (Jurnal Ilmiah Multidisiplin Amsir, 2024)
This research analyzes the utilization of technology and innovation to enhance the sustainability of Sari Tebu Nal SMEs in Parepare City. The research method used is qualitative method with data collection techniques through interviews, observation, and documentation study. The results of the research on sustainable technology innovation strategies in sugarcane juice SMEs can be seen from several aspects, namely innovations made in flavor innovation, packaging, and Social Media technology used in marketing products due to family support to establish sugarcane juice health drink businesses, as well as skills in creating new ideas in product making so that the products produced are highly developed, therefore the stakeholders of Health Drink SMEs need to be facilitated by the government in order to motivate new innovations in products. There needs to be sustainable innovation to create a new innovation so that the business can be widely known to the public and increase business revenue.